2014
DOI: 10.2495/cr140691
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of different sensors for turnout detection for train-borne localization systems

Abstract: Safe railway operation requires a reliable localization of trains in the railway network. Hence, this paper aims to improve the accuracy and reliability of train-borne localization systems proposed recently. Most of these approaches are based on a global navigation satellite system (GNSS) and odometers. However, these systems turned out to have severe shortcomings concerning accuracy and availability. We believe that the ability to detect turnouts and the branching direction thereon is the most valuable clue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The eddy current sensor, in principle a metal detector for characteristic railway features, can be used for a switch way detection, as speed or displacement sensor. Sensors such as cameras [14,15] or LIDAR [16,17] can directly identify the different switch ways and contribute to the trackselective result. A study of a tightly coupled localization with raw GNSS data and a track map was shown in [5,18].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The eddy current sensor, in principle a metal detector for characteristic railway features, can be used for a switch way detection, as speed or displacement sensor. Sensors such as cameras [14,15] or LIDAR [16,17] can directly identify the different switch ways and contribute to the trackselective result. A study of a tightly coupled localization with raw GNSS data and a track map was shown in [5,18].…”
Section: Related Workmentioning
confidence: 99%
“…Algorithm: Train Localization (RBPF) Input: GNSS and IMU sensor data Output: topological coord. ( , , ) and train speed (1) load map (2) initialize odometry Kalman filters with zero vector (3) initialize all particles by first GNSS position (30) (4) loop (5) if new measurement(s) available then (6) t i m es t e p : = + 1, Δ = − −1 (7) for all particles do (8) predict odometry KF (19) (9) update KF with speed (8)/acceleration (11) (10) if train is moving then (11) sample displacement from odometry (28) (12) compute map transition (21) (13) get geometry from map (train frame) (22) (14) compute likelihoods (9)/(10)/(14) (15) multiply particle weight by likelihoods (29) (16) else (train is stopped) (17) observe and filter gyroscope bias (18) end if (19) end for (20) normalize weights (27) (21) compute most likely output estimate (31)-(39) (22) if resampling necessary by eff then (23) perform resampling (24) end if (25) end if (26) end loop Algorithm 1: Algorithm of the map-based train localization with GNSS, IMU, and Rao-Blackwellized particle filter.…”
Section: Particle Filtermentioning
confidence: 99%
“…2. Further properties, such as the spot size and beam divergence, or the combination of several lidar sensors go beyond the scope of this article and have been discussed in [15].…”
Section: Requirements On Lidar Sensors and Market Reviewmentioning
confidence: 99%
“…The larger the measurement rate and the smaller the train velocity are, the better the objects are discretized along the track (cf. [15,Fig. 3b]).…”
Section: Requirements On Lidar Sensors and Market Reviewmentioning
confidence: 99%
See 1 more Smart Citation